A magyarországi városhálózat és az EU-csatlakozás - Beluszky, Pál; Győri, Róbert (Tér és Társadalom, 1999)
The conditions, inducements and directions of the development and shaping of urban stock and network changed radically at different times in the last fifty years in Hungary. These processes can take new way about the preparation and fulfilment of EU accession. The main conditions and features of the development of urban network before 1990: the "top-down" control, the homogenisation and concentrated development of city stock, the "model near" pursue, the strong hierarchical process, spatial difference catching to settlement hierarchy. After 1990: settlements enter ,settlement market, location of individual institution is dominated by conditions of competitive market, the regional structure of the country and the background of settlement devel- opment has been transformed, the significance of administration levels to city development has been de- creased (the importance of city title and the distributor role of counties has been depreciated), the difference between budget supports has been reduced, the role of national concepts has been decreased in settlement development process. The paper review the state of the Hungarian urban network shaped under this terms in the 1990s (town hierarchy, dynamic of towns, town types), and enumerate the expectable effects of EU accession. It shows that "town competition" is increasing (for obtainable supports), the role of county seats wills probably decrease, and the differences between the towns in respect of development level may get larger.